The history of neuro-ophthalmology in Edinburgh. Part II. - Grzybowski, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The Edinburgh Medical School occupies a unique position in the history of medicine. It gave the three famous clinicians and scientists, who significantly developed the fundamentals of neuro-ophthalmology: Sir Charles Bell, Douglas Argyll Robertson and Harry Moss Traquair.